The factors and implications of body image dissatisfaction among adolescents - Nordiana Terence (Scientific Research Publishing, 2024)
This study conducts a comprehensive analysis of the elements that contribute to body image dissatisfaction among teenagers, along with the resulting consequences. Adolescents often encounter social pressures, media influence, peer comparisons, parental expectations, and personal views that affect their perceptions of their own body image. Adverse impressions of one’s body image may result in diminished self-esteem, psychological problems, and a general state of health and happiness. Interventions such as cognitive behavioural therapy (CBT), counselling services, and resilience-building programs are crucial for resolving body image dissatisfaction and fostering a positive self-image among teenagers. Gaining a comprehensive understanding of these elements is crucial for devising specific treatments aimed at assisting teenagers in strengthening their body image and self-esteem, eventually improving their general well-being and quality of life.